Preferences for Bundled Index-Based Livestock Insurance: Evidence From Northern Kenya - Shikuku, Kelvin Mashisia; Ochenje, Ibrahim; Osiemo, Jamleck; Banerjee, Rupsha R.; DuttaGupta, Tanaya; Khalai, Duncan (Wiley, 2026)
Considerable attention has been placed on bundled index insurance to enhance climate resilience, address multiple risks simultaneously, and increase the adoption of agricultural technologies. We conducted an endow-and-exchange choice experiment with 1,828 female and male livestock keepers in northern Kenya to elicit their preferences for bundled index-based livestock insurance (IBLI). We measured relative willingness to pay (WTP) as the maximum amount of money that an individual is willing to pay to switch from one bundle to another. We found that livestock keepers were willing to pay 19% – 33%, 100% – 153%, and 148% – 232% more for IBLI + animal nutrition, IBLI + animal health, and IBLI + flexible package, respectively, relative to IBLI + animal breed. Relative to the average WTP to switch from other bundles to IBLI + animal breed, women had 36% – 45%, 54% – 64%, and 76% – 84% higher WTP than men for IBLI + animal nutrition, IBLI + animal health, and IBLI + flexible package, respectively. Providing information about bundled products and seasonal vegetation forecasts reduced the relative WTP for IBLI + animal nutrition. Our findings highlight the importance of considering the differential preferences of women and men when designing and promoting bundled IBLI products.